2011
DOI: 10.1007/s10029-011-0881-2
|View full text |Cite
|
Sign up to set email alerts
|

Prophylactic antibiotic use in elective inguinal hernioplasty in a trauma center

Abstract: In our settings antibiotic prophylaxis has no significant effect on the incidence of SSI in elective repair of inguinal hernias with mesh. The most effective way to reduce the incidence of infection in prosthetic repair may be a specific center for treatment of abdominal wall hernias.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(33 citation statements)
references
References 32 publications
1
32
0
Order By: Relevance
“…They concluded that antibiotic prophylaxis has no benefit in the incidence of SSI in elective repair of inguinal hernias with mesh. 18 Similar results were documented by Jain et al, 19 Tzovaras et al, 20 and Aufenacker et al, 21 which did not support the use of prophylactic antibiotics in low-risk patients with inguinal mesh hernioplasty.…”
Section: Discussionsupporting
confidence: 86%
“…They concluded that antibiotic prophylaxis has no benefit in the incidence of SSI in elective repair of inguinal hernias with mesh. 18 Similar results were documented by Jain et al, 19 Tzovaras et al, 20 and Aufenacker et al, 21 which did not support the use of prophylactic antibiotics in low-risk patients with inguinal mesh hernioplasty.…”
Section: Discussionsupporting
confidence: 86%
“…This analysis concluded that there was a significant benefit associated with prophylaxis [7]. One further RCT has recently been reported: this small study found no significant difference in risk of infection between use of prophylaxis and placebo [8]. Drawing from such conflicting evidence, there is understandable inconsistency between clinical guidelines: in England and Wales, the National Institute of Clinical Excellence (NICE) recommend the use of antibiotic prophylaxis in clean surgery with implanted material [9] but guidelines issued by the Scottish Intercollegiate Guideline Network (SIGN) state that antibiotic prophylaxis is not needed in inguinal hernia repair with or without implanted mesh [10].…”
Section: Introductionmentioning
confidence: 99%
“…10 Another RCT has found no significant difference in risk of infection between use of prophylaxis and placebo. 11 Because of the differing conclusions from various studies, the clinical guidelines vary. The National Institute of Clinical Excellence (NICE) recommend the use of antibiotic prophylaxis in clean surgery with implanted material.…”
Section: Discussionmentioning
confidence: 99%